Aspects of Technological Modernization of Forestry Enterprise - STYGUN, DINA IGOREVNA; STYGUN, ALEKSANDR VIKTOROVICH; KHASHIR, BELLA OLEGOVNA (The journal of contemporary issues in business and government, 2021)
The economic reality today is such that capitalization of the potential of robotics, biotechnology, digital technologies can lead to a technological revolution, to an explosive growth in labor productivity, which will lead to the restructuring of a number of industries, the depreciation of many production assets, a change in demand for professions, and increased competition. The experience of a number of countries has shown that an increase in the rate of economic development is possible only due to an innovative and technological breakthrough associated with the improvement of productive forces, a radical increase in the technological level, technological re- equipment of economic sectors, an increase in the share of high- and medium-tech industries, while technological modernization determines the economy's susceptibility to innovation activity. The progressive development of technological modernization in a highly competitive environment can bring the economy of the Russian Federation to a new level of development that meets the requirements of the time.